The enhancement of plant disease resistance using CRISPR/Cas9 technology - Mohd Azman, Amier Asyraf; Mohammad Fouad Iskandar,, Haziq Iskandar; Muhammad Zaidi Leong, Muhamad Nur Hafiz Leong; Mohd Fauzi, Noor Akhmazillah (Penerbit UTHM, 2022)
The technologies relating to genome editing have so far progressed rapidly as it has shown the importance of the implementation towards the build up of plan resistance towards pathogens infection. For the past recent years, multiple methods for site directed modification such as clustered regularly interspaced short palindrome repeats (CRISPR)/CRISPRassociated protein 9(cas9), zinc finger nucleases (ZFNs) and transcription activatorlike effector nucleases (TALENs). Among the example methods, CRISPR/Cas9 has by far produced the best result due to the criteria it possessed such as higher success rate, easier design and implementation, less expensive and more versatile. This chapter will revolve around the CRISPR/Cas9 as how the methods will bring forth the advancement of plant protection against potential diseases. An achievement towards the viral diseases resistant on two main species (Arabidopsis and Nicotiana benthamiana) was highlighted to bring upon discussion. with the viral genome. The modification of crop species such as tomato, wheat, rice and citrus are some of the possible targeted CRISPR/Cas9 modifications.